Boosting Fast Sodium Ion Storage by Synergistic Effect of Heterointerface Engineering and Nitrogen Doping Porous Carbon Nanofibers (Small 13/2022). Issue 13 (1st April 2022) - Zhang, Qi; Zeng, Yaping; Ling, Changsheng; Wang, Liu; Wang, Zhiyong; Fan, Tian‐E; Wang, Heng; Xiao, Jianrong; Li, Xinyu; Qu, Baihua
Abstract : Energy Devices In article number 2107514, Yaping Zeng, Zhiyong Wang, Baihua Qu, and co‐workers use heterostructure engineering to boost the fast sodium ion transportation, combined with embedding the heterojunctions into the nitrogen‐doped porous carbon fibers (CNFs), the obtained Sb‐Fe‐S@CNFs composite delivers a desirable reversible capacity and exhibits an ultra‐long high rate cycle life for 16 000 cycles at 10 A g −1 . Heterojunction synergy is an effective approach to improve battery performance.